Self-repair and motivation in legal and medical simultaneous interpreting: reflections from student Interpreters - Şener Erkırtay, Olcay (English Studies at NBU, 2025)
The present study examines the similarities and differences in the use of self-repairs by student interpreters during simultaneous interpreting of two different speech types, medical and legal, as well as the underlying motivations behind these repairs. With this aim in mind, this case study involves an English-to-Turkish simultaneous interpreting experiment with 7 senior student interpreters enrolled in Simultaneous Interpreting course at a major university in İzmir, Türkiye, and corroborated with a post-experiment questionnaire and student reflective reports within the scope of Schön’s concept of “reflection”. Shen and Liang’s taxonomy of self-repair strategies was used for data analysis, and findings were then discussed in line with Daniel Gile’s Effort Model. The findings revealed that challenges arising from syntactic asymmetries, cognitive load, and short-term memory triggered student interpreters’ self-repairs during the interpreting process. As for the self-repair strategies, repetition comes forward as the most commonly used type in both speech types, yet there is a statistical difference between the total number used in the legal and the medical speech. Furthermore, the students’ statements showed no correlation between the number of self-repairs, speech difficulty, and perceived interpreting performance. This finding suggests that self-repair is not always an indicator of poor interpreting performance and error correction; instead, it can serve as a cognitive strategy to manage time, achieve semantic clarity, and enhance the comprehensibility of renditions.